Digitalisation of Education: Challenges and Issues in Virtual Pedagogical Competence - Alam, Sohaib; Hameed, Ansa; Balogh, Zoltan; Haque, Shafey Anwarul (Journal of Education Culture and Society, 2025)
Thesis. Teachers have been tasked with using digital tools in their classrooms to prepare universities for the challenges of the twenty-first century. The present study explored the nuances of digital pedagogy and competence, aiming at teachers teaching English skill courses using digital platforms, consisting explicitly of cultural, societal, interpersonal, and moral concerns related to acquiring knowledge with and from digital technologies to emphasise the praxis of digital competencies. Concept. Pedagogues in higher education have used digital means during the pandemic, resulting in a number of teaching-learning platforms to promote efficient learning outcomes. The study found information and communication technology (ICT)-based instructional designs that supported exceptional educational outputs; however, there are issues and problems with the virtual modus operandi. Results and conclusion. This research examines issues and challenges in digital teaching and how it affects in-service teachers’ perceptions of digital education technology. The study uses a qualitative method by interviewing teachers at the undergraduate level in Saudi Arabia to gather information about teachers’ perceptions. Twenty-nine (29) teachers participated in the study, teaching English skills courses at Prince Sattam Bin Abdulaziz University. The findings indicate that there is a need for in-service training of teachers on the different platforms that are being used to teach the English language. Moreover, the key findings of the present study are the unavailability of immediate feedback, less interaction, fear of technology-driven pedagogy, and difficulty in practice-driven exercises.